The Transformation of School Culture Based on Spiritual Values as an Effort to Improve Student Discipline - Muh Habibulloh; Muh Ali Ridho; Nur ‘Azah; Muhammad Yusron Maulana El-Yunusi; Mardiyah (International Journal of Education Management and Religion, 2024)
The school’s culture, encompassing norms and traditions, plays a pivotal role in shaping student behavior and fostering discipline. Integrating spiritual values into the school culture holds significant potential to enhance student discipline while simultaneously shaping their moral and ethical character. This study examines how a school culture rooted in spiritual values can contribute to improving student discipline, mitigating negative behaviors such as disobedience and bullying, and fostering a conducive learning environment. This research adopts the Library Research method, which involves the systematic collection and analysis of relevant literature, including books, journals, theses, and previous studies. Data were sourced from reputable academic databases such as Google Scholar, JSTOR, and ProQuest, with a focus on exploring the interplay between school culture, spiritual values, and student discipline. The key findings reveal that the consistent application of spiritual values in both academic and extracurricular activities positively influences student behavior, enhances their adherence to rules, and strengthens personal commitment to ethical principles. The study concludes that transforming school culture through the integration of spiritual values is an effective strategy for fostering student discipline and character development. Achieving this transformation requires the collective support of all stakeholders, including teachers, students, and parents, as well as ongoing evaluation to ensure its sustained success. The findings offer valuable insights for educational institutions seeking to design programs that embed spiritual values into their culture to nurture disciplined, responsible, and morally upright students.